Prospective biology teachers’ readiness for implementing the Merdeka Curriculum through microteaching learning tools - T. Titin; Kurnia Ningsih; Eko Sri Wahyuni; Mas Akhbar Faturrahman; Delvia Uliyanda; Dian Wahyuningsih (Research and Development in Education (RaDEn), 2025)
The Merdeka Curriculum emphasizes flexibility in creating learning activities that accommodate student development, leverage technology, and strengthen Pancasila values. Prospective teachers’ readiness to implement the Merdeka Curriculum can be confirmed through the Microteaching course. This research aims to determine the readiness of prospective biology teachers at Universitas Tanjungpura to implement the Merdeka Curriculum by examining their difficulties in developing biology learning tools in the Microteaching course. This research is classified as mixed method and involved 47 Biology Education students at Universitas Tanjungpura as the sample, taken through total sampling. The data collection technique used was a validated questionnaire consisting of eight aspects: “Development of Teaching Materials,” “Dimensions of the Pancasila Student Profile,” “Clarity of Learning Objectives,” “Organization of Learning Content,” “Learning Media and Student Worksheets,” “Learning Syntax,” “Assessment,” and “Evaluation and Follow-up Actions.” The overall average is 78.44%, with the highest in the “Clarity of Learning Objectives” aspect (81.78%, strongly ready) and the lowest in the “Assessment” aspect (74.20%, ready). The results indicate that Biology Education students at Universitas Tanjungpura are ready to develop biology learning tools for the Merdeka Curriculum. However, the results also suggest the need to strengthen prospective biology teachers’ holistic understanding of the Merdeka Curriculum.